Darragh Morgan & John Tilbury, Morton Feldman—For John Cage (Diatribe Records: 2020); Benjamin Dwyer, What is the Word, Diatribe Records (Diatribe Records: 2020); Lina Andonovska, A Way A Lone A Last (Diatribe Records:2020) - Diovanni, Timothy (Journal of the Society for Musicology in Ireland, 2020)
A review of Darragh Morgan and John Tilbury: Morton Feldman—For John Cage, Diatribe Records (2020), (Digital Album) DICCD025; Benjamin Dwyer: What is the Word, Diatribe Records (2020), (Digital Album) DIACD031; and Lina Andonovska: A Way A Lone A Last, Diatribe Records (2020), (CD and Digital Album) DIACD026